First-Year Students Background and Academic Achievement: The Mediating Role of Student Engagement - Ribeiro, Luísa; Rosário, Pedro; Núñez, José Carlos; Gaeta, Martha; Fuentes, Sonia (Frontiers in Psychology, 2019)
The current study aimed to analyze the relationships between students’ background variables (students’ academic preparation and sociocultural status), students’ cognitive and behavioral engagement, and an outcome variable (academic achievement). One sample of 380 first year students, who were studying in different scientific areas, participated in the study. Students answered a questionnaire at the beginning and at the end of their first semester in college. To increase ecological validity, students’ cognitive and behavioral engagement and academic achievement were assessed using a specific curricular subject of the course as a reference. Students’ grades were collected through academic services. Data from both time points were analyzed with a structural equation model (SEM) and data showed a goodness of fit of SEM in both time points. Findings indicate that cognitive and behavioral engagement mediated the relationship between students’ background variables and their academic achievement. The analysis of both SEM allows us to understand that academic achievement at the end of the semester is closely related to what happens at the beginning of the semester (e.g., approach to learning, study time). Thus, promoting students’ engagement at the beginning of the semester should be considered a priority, as the first part of the first semester represents a critical period for students and for their integration in college. Thus, universities should consider improving their mechanisms of collecting information to allow for early identification, support, and monitoring of students at risk of dropping out, showing high level of disengagement and low academic achievement.